EEG Microstates Change in Response to Increase in Dopaminergic Stimulation in Typical Parkinson’s Disease Patients - Serrano, J. Ignacio; del Castillo, María Dolores; Cortés, Verónica; Mendes, Nuno; Arroyo, Aida; Andreo, Jorge; Rocon, Eduardo; del Valle, María; Herreros, Jaime; Romero, Juan Pablo (Frontiers in Neuroscience, 2018)
Abstract Objectives Characterizing pharmacological response in PD patients may be a challenge in early stages but gives valuable clues for diagnosis. Neurotropic drugs may modulate Electroencephalography (EEG) microstates (MS). We investigated EEG-MS default-mode network changes in response to dopaminergic stimulation in Parkinson’s disease (PD). Methods Fourteen PD subjects in HY stage III or less were included, and twenty-one healthy controls. All patients were receiving dopaminergic stimulation with levodopa or dopaminergic agonists. Resting EEG activity was recorded before the first daily PD medication dose and one hour after drug intake resting EEG activity was again recorded. Time and frequency variables for each MS were calculated. Results PD subjects MS A duration decreases after levodopa intake, MS B appears more often than before levodopa intake. MS E was not present, but MS G was. There were no significant differences between control subjects and patients after medication intake. Conclusions Clinical response to dopaminergic drugs in PD is characterized by clear changes in MS profile. Significance This work demonstrates that there are clear EEG MS markers of PD dopaminergic stimulation state. The characterization of the disease and its response to dopaminergic medication may be of help for early therapeutic diagnosis.